1988
DOI: 10.1172/jci113431
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 induces a shock-like state in rabbits. Synergism with tumor necrosis factor and the effect of cyclooxygenase inhibition.

Abstract: In addition to activating T and B lymphocytes, interleukin 1 (IL-1) induces several hematologic and metabolic changes typical of host responses to infection and injury. We now report a new biological property, namely, the induction of hypotension. Rabbits given a single intravenous injection of recombinant human IL-I-beta (5 isg/kg) rapidly developed decreased systemic arterial pressure, which reached the lowest levels after 50-60 min and slowly returned to pre-IL-I values after 3 h. Associated with the hypote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
298
0
16

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 934 publications
(330 citation statements)
references
References 35 publications
14
298
0
16
Order By: Relevance
“…It has also been reported that high concentrations of pro-inflammatory cytokines correlate with the prognosis of sepsis and the development of multiple organ dysfunctions (Edith et al 2004). Moreover, the infusion of high concentrations of pro-inflammatory cytokines in rabbits was associated with multiple organ dysfunction syndrome (Kusawa et al 1988). Several studies have suggested that the circulating levels of proinflammatory cytokines could be useful in assessing the severity and in predicting the clinical outcomes of some diseases (Rauchhaus et al 2000;Orro et al 2011;El-Ashker et al 2013;El-Ashker et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that high concentrations of pro-inflammatory cytokines correlate with the prognosis of sepsis and the development of multiple organ dysfunctions (Edith et al 2004). Moreover, the infusion of high concentrations of pro-inflammatory cytokines in rabbits was associated with multiple organ dysfunction syndrome (Kusawa et al 1988). Several studies have suggested that the circulating levels of proinflammatory cytokines could be useful in assessing the severity and in predicting the clinical outcomes of some diseases (Rauchhaus et al 2000;Orro et al 2011;El-Ashker et al 2013;El-Ashker et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models for inducing the toxicshock-like state usually use high doses of TSST-1, ranging from microgram to milligram quantities per kilogram of body weight [23], and under these con ditions, circulating IL-1 is clearly being produced [3]. Using anesthetized rabbits our previous studies dem onstrated that low doses of IL-1 induce reversible hypotension and, when given as a constant infusion, a shock-like state [16]. The time course of IL-l-induced hypotension was rapid, and the onset and recovery were nearly identical to those of pyrogenic responses [24].…”
Section: Discussionmentioning
confidence: 99%
“…Fe male New Zealand white rabbits (weighing ^5 kg) were anesthetized with a single injection of 4 mg of xylazine/kg and 10 mg of ketamine/kg. This com bination of nonbarbituates has been used in previ ous studies in models of septic shock where experi mentally induced changes in hemodynamic parameters were shown to be unaffected by these anesthetics [16]. Catheters were placed in the left carotid artery (PE 50), the pulmonary artery (no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One obvious confounding factor is the lack of possible interactions with other mediators, which cannot be taken into account. In in vitro systems this is not a theoretical concern, as it has repeatedly been found that inflammatory mediators may have additive or synergistic effects that markedly differ from their individual biological activities [5].…”
Section: Models Of Experimental Bacteraemia or Endotoxaemia And Activmentioning
confidence: 99%